Risk Analysis of Typhoid Fever Based on Personal Hygiene and Street Food Consumption Habit at Home - Hilda Nuruzzaman; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2016)
Typhoid fever is a disease caused by Salmonella typhi bacteria that is transmitted through contaminated food and drink. Data from the Regional Public Hospital (RSUD) dr. Abdoer Rahem shows that from 2011-2013 the incidence of typhoid fever has always increased and is often found at the age of 5-14 years. This study aims to analyze the risk of typhoid fever based on personal hygiene and snacking habits at home in children aged 7-12 years. This research is an observational analytic study with case-control study design. The data of this study were taken from the lotus unit medical records last 1 year at the RSUD dr. Abdoer Rahem Situbondo, while the control is a neighbor of the case. The research sample was 80 people. The results showed that the greater risk of typhoid fever with poor handwashing habits after defecation at home (OR = 3.67; 95% CI = 1.29-10.64), poor handwashing habits before eating at home (OR = 4.33; 95% CI = 1.54 –12.44), dirty short nails (OR = 7.79; 95% CI = 1.46–46.18) often get snacks when at home (OR = 3.89; 95% CI = 1.39–11.06), buy snacks at street vendors when at home (OR = 3.95; 95% CI = 1.40–11.30), snack packages that open when bought at home (OR = 3.5; 95% CI = 1.26-9.93). The good habit of washing hands after defecation and before eat, as well as the condition of clean short fingernails, rarely snack when at home, buy snacks at the supermarket, and buy snacks with a closed snack condition when at home can reduce the risk of typhoid fever in children aged 7 - 12 years.